Digital Partograph: A Way of Improving Quality of Partograph Use During Labour Monitoring Process - Ningrum, Widya Maya (Ikatan Bidan Indonesia (IBI), 2024)
Partographs are one of the ways to improve labor outcomes. In the meantime, the use of paper as media has been regarded as barriers that prevent it from fully utilized. Furthermore, this paper reports the quality of applications that was originally designed by the researchers as an android based application that intends to lessen passing and injury in labor used for monitoring labour progress and depicts the plan and fundamental assessment of the computerized partograph. Moreover, this study used a descriptive method and included 45 respondents, all of them used the digital partograph by using cases as data that is used to be filled into the digital partograph. Furthermore, the data were collected by distributing an ISO/IEC 9126 questionnaire and analyzed using expressive investigation strategies. Therefore, Aftereffects of this review demonstrate that among quality elements of the advanced partograph, usefulness is the most elevated. Furthermore, through exploratory examination and a client focused plan measure, we made and created computerized partograph to help with quality checking care in labor wards